1
$\begingroup$

I was working on an examples from my textbook concerning transforming formulae into disjunctive-normal form (DNF) until I found an expression that I cannot solve. I hope somebody can help me transform the following statement into DNF:

$$ (\lnot q \lor r) \land ( q \lor \lnot r)$$

$\endgroup$
4
$\begingroup$

$$ (\lnot q \lor r) \land ( q \lor \lnot r)\tag{1}$$ $$[(\lnot q \lor r) \land q] \lor [(\lnot q \lor r) \land \lnot r]\tag{2}$$ $$[(\lnot q \land q) \lor (r \land q)] \lor [(\lnot q \land \lnot r) \lor (r \land \lnot r)]\tag{3}$$ $$ \text{False} \lor (r \land q) \lor (\lnot q \land \lnot r) \lor \text{False}\tag{4}$$

$$(q \land r) \lor (\lnot q \land \lnot r)\tag{5}$$

Note that $(5)$ is is in disjunctive normal form (DNF), and is equivalent to $(1)$.

$(1) \to (2)$: Distribution;
$(2) \to (3)$: Distribution, twice;
$(3) \to (4)$: Contradictions $\lnot q \land q \rightarrow \text{False}$ and $\lnot r \land r\rightarrow \text{False}$;
$(4) \to (5)$: Simplification (removal of contradictory disjuncts).

Observation: both $(1)$ and $(5)$ are equivalent to $q \leftrightarrow r$:
To see this, you can rewrite $(1)$ as: $$(\lnot q \lor r) \land (\lnot r \lor q) \iff (q \rightarrow r) \land (r\rightarrow q) \iff (q \leftrightarrow r).$$

$$q \leftrightarrow r\; \text{ is true if and only if }\;(q \land r) \text{ is true or}\; (\lnot q \land \lnot r)\text{ is true.}$$ $$\text{That is,}\;q \leftrightarrow r\; \text{ is true if and only if }\;\;(q \land r) \lor (\lnot q \land \lnot r).\tag{5} $$

p | q |$\;\lnot q \lor r$ | $q \lor \lnot r\;$|$\;(\lnot q \lor r) \land (q\lor \lnot r)$
T | T | $\quad$T $\quad$|$\quad$ T $\quad$| $\quad\quad\quad\quad$T$\quad\quad\leftarrow\quad\;\; (q \land r)$
T | F | $\quad$F $\quad$|$\quad$ T $\quad$| $\quad\quad\quad\quad$F
F | T | $\quad$T $\quad$|$\quad$ F $\quad$| $\quad\quad\quad\quad$F
F | F | $\quad$T $\quad$|$\quad$ T $\quad$| $\quad\quad\quad\quad$T$\quad\quad\leftarrow\quad (\lnot q \land \lnot r)$

$\endgroup$
4
$\begingroup$

Make a table

 q  r  result
 0  0     1
 0  1     0
 1  0     0
 1  1     1

Now you can get the DNF formula, by "or-ing" all the rows with result=1: $$ (\lnot q \land \lnot r ) \lor ( q \land r )$$

$\endgroup$
1
$\begingroup$

Think of it as an expression with $+$ and $\cdot$ and use the distributive law (I'll use $q'$ as notation for $\neg q$:

$(q' + r)(q + r') = q'q + q'r' + rq + rr' = q'r' + rq$

I cancelled $q'q$ and $r'r$ because $q$ cannot be true and false (and same for $r$). With your symbols, this gives

$(\neg q \wedge \neg r) \vee (r \wedge q)$

You can (and should) check that this is correct with a truth table.

$\endgroup$
1
$\begingroup$

By the distibution law one obtains $(\lnot q \lor r) \land ( q \lor \lnot r) \leftrightarrow ((\lnot q \lor r) \land q) \lor ((\lnot q \lor r) \land \lnot r) \leftrightarrow (\lnot q \land q) \lor (r \land q)\lor (\lnot q \land \lnot r) \lor (r \land \lnot r)\leftrightarrow (r \land q)\lor (\lnot q \land \lnot r)$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.